Methodological Pathways to Improvements of Evaluation Approaches: The Case of Irrigated Agriculture Performance Evaluation - Anne Chaponnière; Serge Marlet; Sylvain R. Perret; Gabrielle Bouleau; Abdelaziz Zaïri (Journal of MultiDisciplinary Evaluation, 2012)
Background:  Irrigated agriculture is often evaluated but few reviews of evaluation methodology adapted to this object are available in the literature. Besides, recommendations to improve evaluation in this field are lacking.